MENGIDENTIFIKASI UPAYA LAYANAN PENDIDIKAN BAGI ANAK BERKEBUTUHAN KHUSUS DI TK HARDIKA JAYA - Kadek Trina Des Ryantini; Luh Putu Dian Kresnawati (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Currently, the number of children with special needs in Buleleng Regency is quite significant, there are 331 individuals. This number is disproportionate to the availability of special education schools. This situation necessitates immediate attention to ensure that children with special needs continue to receive educational services. As a non-inclusive institution, Hardika Jaya Kindergarten has been offering educational services catering to the specific needs of children with disabilities. This qualitative descriptive study delves into the nature of these services and the challenges encountered by the teaching staff in their implementation. Six teachers from Hardika Jaya Kindergarten served as the participants for this research. Data was collected through a combination of document analysis, questionnaires, and observational notes. Subsequent analysis involved processes of data reduction, categorization, and verification, all within a qualitative descriptive framework. The research findings indicate that the educational services provided for children with special needs at TK Hardika Jaya are similar to those provided for regular children, starting from lesson planning, management, and evaluation. However, the challenges encountered include teachers having difficulty understanding children's interests; children being unable to focus; children having difficulty interacting; and teachers not yet receiving training as special education teachers for children with special needs.